THE USE OF TOTAL PHYSICAL RESPONSE STORYTELLING METHOD IN TEACHING ENGLISH VOCABULARY TO YOUNG LEARNERS - Yasin Firmansyah (ReALL - Research on Applied Linguistics and Literature, 2024)
The research was motivated by students who found obstacles in the form of difficulties in acquiring English vocabulary. This research aims to find out how significant the Total Physical Response Storytelling method is in teaching English vocabulary to young learners and to investigate the students’ response toward the implementation of TPRS method in their class. This study is a quasi-experimental design. Non-equivalent design control group is applied in this research. The data of this study were collected from experiment and control groups by giving the test in the form of pre-test and post-test. The data were analysed by using t-test, meanwhile the data of questionnaire were analysed by using Likert Scale. The result stated that the difference of students’ achievement between TPRS Method and Conventional Method in improving students’ English vocabulary is significant. Furthermore, the score of experiment class is higher than the control class. Overall, it can be concluded that the improvement of students’ English vocabulary by using Total Physical Response Storytelling method is very significant. To sum up, the use of TPRS in teaching English vocabulary to young learner is not only effective but also presents the enjoyable experience to the students.